RADIAL KERATOTOMY: EFFECTS OF CORNEAL THICKNESS ON FINAL OUTCOME - Raja, Naseer; Niazi, Muhammad Khizar; Karamat, Sobia (Journal of Ayub Medical College Abbottabad, 2003)
Background: Corneal thickness may contribute in the final outcome of radial keratotomy operation for the correction of myopia. We present our study on ninety-nine consecutive eyes with a mean follow-up of one year. Methods: Ninety-nine eyes with preoperative/uncorrected Myopia between 2.5-6.0D and a mean age of 29.2 (±7) years underwent radial keratotomy between January 1999-December 2001 in the Department of Ophthalmology, Military Hospital, Rawalpindi. The eyes were divided based on their corneal thickness into group-A (51 eyes), with a pachymeter reading of 500-540 µm, and Group-B (48 eyes), with a pachymeter reading of 541-580 µm. The comparison between the Postoperative visual acuity of two groups was made at the end of study after one years` follow up. Results: Forty-five eyes (88.23%) in Group-A improved to an uncorrected acuity of 20/20 as compared to forty eyes (83.33%) in Group-B (p>0.05). Hyperopic shift occurred in two eyes (3.92%) in Group-A, as compared to ten eyes (20.83%) of Group-B (p>0.05). Refraction showed that 94.11% cases of Group-A to be within 1 diopter of Emmetropia as compared to 93.75% cases in Group-B. Similarly, 98.03% cases of Group-A were within 2 diopters of Emmetropia as compared to 95.83% cases of Group-B. Glare and variation of vision in the initial four weeks were the most frequently reported complications in both groups. Conclusion: Thickness of cornea does not significantly affect the outcome of surgery in cases of low to moderate degrees of myopia. KEYWORDS: Radial Keratotomy, Corneal Thickness, Myopia